2014
DOI: 10.1080/00071005.2014.918576
|View full text |Cite
|
Sign up to set email alerts
|

Learning as Researchers and Teachers: The Development of a Pedagogical Culture for Social Science Research Methods?

Abstract: In light of calls to improve the capacity for social science research within UK higher education, this article explores the possibilities for an emerging pedagogy for research methods. A lack of pedagogical culture in this field has been identified by previous studies. In response, we examine pedagogical literature surrounding approaches for teaching and learning research methods that are evident in recent peer-reviewed literature. Deep reading of this literature (as opposed to systematic review) identifies di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 33 publications
4
104
0
8
Order By: Relevance
“…Thus, our data show frequent references to learningthrough-doing, student-centred, active or problem-based learning. This resonates with the wider literature on methods education (Kilburn, Nind, and Wiles 2014). It also resonates with some of the key messages coming from the inclusive education literature where teachers are seeking to support learners' skills development to enable them to act competently, not as researchers as in the case of methods education, but simply as learners (Hart et al 2004;Florian and Linklater 2010).…”
Section: Holistic Approachesmentioning
confidence: 60%
See 2 more Smart Citations
“…Thus, our data show frequent references to learningthrough-doing, student-centred, active or problem-based learning. This resonates with the wider literature on methods education (Kilburn, Nind, and Wiles 2014). It also resonates with some of the key messages coming from the inclusive education literature where teachers are seeking to support learners' skills development to enable them to act competently, not as researchers as in the case of methods education, but simply as learners (Hart et al 2004;Florian and Linklater 2010).…”
Section: Holistic Approachesmentioning
confidence: 60%
“…Applying a lens of critical or inclusive pedagogy to a consideration of the teaching and learning of research methods means that we make such values explicit. For Alexander (2009, 11), pedagogy is 'the act of teaching together with its attendant discourse', and the discourse of inclusive pedagogy is not often associated with adults learning research methods, where the pedagogical discourse generally is under-developed (Kilburn, Nind, and Wiles 2014). It is mostly in research methods textbooks that we can find an articulation of inclusive values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However there are fewer discussions around undergraduate research where contexts and datasets span, or compare, the natural and social sciences (see, e.g., Jenkins [2009a, 2009b]; Taylor and Wilding [2009]; Russell, Hancock and McCullough [2007]; Kinkead [2003]; Hathaway, Nagda and Gregerman [2002]) and far fewer examples that focus solely on the social sciences (see, e.g., Kilburn, Nind and Wiles [2014]; Todd, Bannister and Clegg [2004]; Ishiyama [2002]). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Earley (2014) found that the literature on research methods pedagogy offered little guidance beyond the insights of individual instructors, courses, or institutions, leaving methods teachers with just their peer networks, an unconnected research literature, and trial-anderror as the basis for developing their practice. Kilburn, Nind, and Wiles (2014) went on to conclude that pedagogical questions were being considered, and even discussed (particularly active, experiential and reflexive learning approaches), but that this did not amount to the 'exchange of ideas within a climate of systematic debate, investigation and evaluation' seen by Wagner, Garner, and Kawulich (2011, 75) to represent a healthy pedagogic culture.…”
mentioning
confidence: 99%